A space-occupying lesion - Ghosh, Amitav (British Homeopathic Journal, 1991)
A patient with a space-occupying lesion is treated with homœopathic medicines. Pathological and constitutional prescribing along with miasmatic medicines are recommended. Prognosis of neoplastic disease, significance of pathophysiology and repertorization and hypothesis on tremor are discussed. For further evaluation of homœopathic treatment of space-occupying lesions, more case reports from readers are suggested.
Keywords: Space-occupying lesion, Glioma, CT scan; Homœopathy; Miasm; Apis; Thuja; Arsenicum; Lycopodium